The relationship of external and internal sidewall dimensions in the adult Caucasian nose12. (3rd January 2013) - Setabutr, Dhave; Sohrabi, Sohrab; Kalaria, Shana; Gordon, Kimberly; Fedok, Fred G.
Abstract: Objectives/hypotheses: : Nasal bone length is commonly referenced in the rhinoplasty literature. It has been suggested that short nasal bone length may predispose one to a greater risk of middle vault collapse after rhinoplasty. However, there are limited data available on what constitutes the normal dimensions of these pertinent structures of the nasal sidewall. In addition, no data exist on the gender and ethnic variability of such dimensions. This article reports on measurements of nasal bones and associated structures in adult Caucasian cadavers and their relationships to the nasal sidewall. Furthermore, this study assesses the validity of using surface measurements to approximate the true dimensions of the nasal sidewall structures. Methods: : Using 37 adult cadavers, stable, external, nasal landmarks were identified and measured to approximate the dimensions of the nasal bones and upper lateral cartilages. These clinically relevant surface landmarks were then evaluated relative to the direct measurements of dissected nasal bones and upper lateral cartilages in a subgroup of 14 cadavers. Results: : For the subgroup, the average length Ainternal (nasal bone) was 24.57 mm; the average measured length Binternal (upper lateral cartilage) was 12.43 mm. Measurements for the subgroup obtained via external landmarks were 20.21 mm (Aexternal ) and 15.67 mm (Bexternal ), respectively. The relationship of the nasal bone internal length to the external measurement (A) was a ratio of 1.22:1, whereas the internal length of the upper lateral cartilage to the corresponding external measurement (B) was 0.79:1. Average external measurements for the total group were 20.43 mm for the nasal bone and 14.30 mm for the upper lateral cartilage. Conclusions: : These data provide useful information to guide the surgeon in avoiding middle vault collapse postoperatively and when evaluating those patients with presurgical middle vault concerns. With less ability to support the upper lateral cartilages, short nasal bones can predispose an individual to middle vault collapse postoperatively.